Elliptical double corrugated tubes for enhanced heat transfer. (January 2019) - Navickaitė, Kristina; Cattani, Luca; Bahl, Christian R.H.; Engelbrecht, Kurt
Highlights: Numerical simulations were performed for a laminar fully developed flow with constant surface temperature. NTU is enhanced by 400% in double corrugated tubes maintaining 4.2 times lower volumetric flow rate. The overall performance increase in double corrugated tubes when compared to a straight tube. The double corrugated tubes increase compactness of a heat exchanger. Abstract: The thermal performance at constant pumping power conditions was numerically investigated in ellipse and super ellipse-based double corrugated tubes. A significant increase in thermal efficiency in double corrugated tubes is accompanied with a reasonable penalty in flow reduction for the cases modelled. An ellipse and a super ellipse-based double corrugated tubes were modelled at laminar fully hydraulically developed incompressible flow. Each base geometry was analysed holding either hydraulic diameter constant or the cross-sectional area constant. The pressure drop was normalized to the length of each modelled tube in order to maintain the pumping power. Thermal analysis was conducted under constant wall temperature boundary condition. The governing equations for non-isothermal flow were solved using the finite element method, and the results of the simulations were normalized to an equivalent straight tube. Numerical results predict a thermal efficiency enhanced by 400% maintaining 4.2 times lower volumetric flow rate in double corrugated tubes at the same pressure drop. The global performance evaluation criterion increases up to 14% for the double corrugated tubes with an ellipse-base and up to 11% for the tubes with super ellipse-base.